Vitamin D Status in Renal Transplant Recipients - Aristeidis Stavroulopoulos; Michael Cassidy; C.J. Porter; D. J. Hosking; Stephanie Roe (2007)
Vitamin D plays an important role in calcium homeostasis. Renal transplant recipients may be more susceptible to reduced levels because of decreased sun exposure and steroid therapy. This study aimed to determine vitamin D status after renal transplantation and its effect on parathyroid hormone (PTH) and bone mineral density (BMD). We measured serum 25-hydroxyvitamin D levels (25-OHD) in 244 renal transplant recipients, divided into two groups, 104 recently transplanted (less than 1 year) and 140 long-term. Vitamin D status was defined according to NKF/KDOQI guidelines. Mean 25-OHD levels were 33 +/- 19 nmol/L and 42 +/- 20 nmol/L, respectively, for the recent and long-term transplant recipients. Vitamin D insufficiency was present in 29% and 43%, deficiency in 56% and 46% and severe deficiency in 12% and 5%, respectively. An inverse correlation was found between logPTH and 25-OHD (r=-0.2, p= 0.019) in long-term but not in recently transplanted patients. No correlation was found between 25-OHD levels and BMD. Hypercalcaemia was present in 40% of the recently transplanted recipients and 25% of the long-term. In conclusion 25-OHD was low in virtually all of our renal transplant recipients and may aggravate secondary hyperparathyroidism, but its correction may be difficult in patients with hypercalcaemia.